Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0118
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Takt Planning and Takt Control Into Residential Construction

Abstract: This study addresses the suitability of takt planning and takt control (TPTC) for the interior phase in residential construction projects. The purpose is to gain understanding on how to best implement TPTC in residential construction.The study was conducted as a qualitative case study, by investigating TPTC implementation for the interior phase in a residential construction project in Finland. The initial motivation for takt implementation was to achieve better flow efficiency and radically shortened productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Material deliveries to the site, storage and hauling of the material on the site are planned, buffered, and managed in a way that materials are available for every takt in time (also suggested by Lehtovaara et al 2019).…”
Section: R5 the Logistics Are Integrated And Takted With The Productmentioning
confidence: 99%
See 2 more Smart Citations
“…Material deliveries to the site, storage and hauling of the material on the site are planned, buffered, and managed in a way that materials are available for every takt in time (also suggested by Lehtovaara et al 2019).…”
Section: R5 the Logistics Are Integrated And Takted With The Productmentioning
confidence: 99%
“…Takt methods such as Takt Time Planning (TTP, e.g., Frandson et al 2013), Takt Planning and Takt Control (TPTC, e.g., Dlouhy et al 2016) have demonstrated the potential of takted production to achieve more stable operations and radically reduced production duration, among other benefits. Successful implementation cases have been reported in various locations -especially in the US (Frandson et al 2013), Germany (Binninger et al 2018), and Norway (Vatne and Drevland 2016) -and most recently, in Finland (Lehtovaara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the vision is also to guide future research proposals submitted to the consortium. Takt in production and design was chosen as the theme for the second research project (Lehtovaara et al, 2019). The decision was based on the international benchmarking study conducted during the first year, which yielded takt production as one of the most promising new methods to radically reduce production durations without increasing costs or compromising quality.…”
Section: Innovations In Constructionmentioning
confidence: 99%
“…That is why the application of takt production requires monitoring production realization at a higher level of detail. Because takt production requires rapid reactions (e.g., [6]) and revising the takt schedule during production is challenging [6,7], it must be monitored closely and in detail [8].…”
Section: Introductionmentioning
confidence: 99%